Boca de cena - Guerreiro, Fernando (Sinais de Cena, 2008)
Recensão de Fernando Guerreiro ao artigo José Oliveira Barata, Fernando Matos Oliveira, Maria Helena Santana (eds.), O melodrama - I, Coimbra, Centro de Literatura Portuguesa, Faculdade de Letras, 2006, 179 pp.